Методичний підхід до оцінювання та відбору венчурних проєктів - Кузьмін, О. Є.; Терлецька, В. О.; Kuzmin, O. E.; Terletska, V. O. (Видавництво Львівської політехніки, 2021)
Досліджено та проаналізовано методичні підходи до оцінювання та відбору венчурних проєктів. Виявлено, що у динамічному середовищі функціонування венчурні фонди вибирають такі стратегії залучення та підготовки угод, які відповідають їх досвіду і становищу на ринку. Сформовано основні етапи відбирання венчурних проєктів, що дає змогу формалізувати процес відбору венчурних проєктів і зробити його максимально прозорим, зрозумілим та простим. Досліджено та систематизовано критеріальну базу показників оцінювання та відбору венчурних проєктів, що дає змогу формалізувати процес їх оцінювання та прийняття раціональних управлінських рішень.

The article examines and analyzes methodological approaches to the evaluation and selection of venture projects, found that in a dynamic environment, venture funds choose strategies to attract and prepare agreements that correspond to their experience and market position. The main stages of selection of venture projects have been formulated, which allows to formalize the process of selection of venture projects and make it as transparent, clear and simple as possible. The criterion base of indicators of evaluation and selection of venture projects has been investigated and systematized, which allows to formalize the process of their evaluation and making rational management decisions. Attracting and preparing agreements is one of the most important aspects of venture activity, which requires high competence, skills and abilities. Analysis of the scientific literature made it possible to identify different approaches to the evaluation and selection of venture projects. For evaluation and selection of venture projects, first of all, qualitatively prepared business plans are studied. In this case, applications for investment without a business plan are usually not considered by the funds at all. In such conditions, investors are helped by knowledge in the relevant sectors of the economy and understanding of the prospects for their development, this is equated with a preliminary discussion of the problem with colleagues or at meetings of fund managers, where a deeper assessment of business value. The main principles of assessing the effectiveness of investment in venture investment are: taking into account the specifics of the investment sector in order to calculate the payback period of investments and the level of their profitability, which is as close as possible to real; in the presence of a base of comparison of application of benchmarking; optimization of fund management costs; taking into account all financial flows of the project; comparison of the cost of borrowed capital and return on investment; reasonable distribution of financial resources between venture projects taking into account the criterion of their effectiveness, etc. The purpose of the examination of an innovative venture project is to assess the scientific and technical level of the project, the possibilities of its implementation and effectiveness, the consequences of its implementation. Based on the results of the study, decisions are made on the feasibility and volume of investment, which determines the basic principles of the examination, namely: the system of organization of expert work and the unity of its regulatory and methodological support; independence and legal protection of participants in the expert process, their competence and interest in obtaining objective results; scientific and economic substantiation of expert assessments, their orientation to the world level of development of science and technology, norms and rules of technogenic and ecological safety, requirements of standards and international agreements; objectivity of the received decisions according to results of examination. The main criteria for selecting a venture project are a well-prepared business plan, scientific and technical level of the project, its feasibility and effectiveness, and important indicators for evaluating the effectiveness of a venture project are indicators of internal rate of return, modified internal rate of return, net present value, payback period , discounted payback period, profitability of sales, the average rate of return.
Methodical approach to evaluation and selection of venture projects
Keywords: венчурні проєкти; відбір венчурних проєктів; оцінювання венчурних проєктів; venture projects; selection of venture projects; evaluation of venture projects; 330.322; 330.3563